SIMPLIFIED CALCULATION OF MESHING STRENGTH OF FACE GEAR PAIR (MT) - HE Fei; QIAN WeiXiang; FU XueZhong; PENG XianLong (Jixie qiangdu)
In order to facilitate the selection of basic parameters in the initial design stage of face gear, and simplify the process of solving meshing strength of face gear pair. By referring to the existing strength calculation formula of the standard spur gear, the analytical calculation models of contact stress and bending stress of full tooth height of face gear were established. The curvature of tooth surface was solved by the basic parameters of the gear, and the contact stress of tooth surface was solved by the Hertz contact theory. The tooth thickness at the dangerous section of gear teeth was determined by the 30° tangent method, and the stress calculation coefficient table was given based on the expression of basic parameters of gear pair, finally, the analytical calculation formula of tooth root bending stress was deduced. Taking face gear pair with a certain design parameter as an example, the results obtained from the analytical calculation models were compared with those from the finite element simulation to verify the accuracy of models. On this basis, a simplified formula for calculating the strength of face gear was given which can be directly solved by the basic parameters of gear.